2019
DOI: 10.1177/2396941519863984
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relationships between lexical and syntactic skills of children with Developmental Language Disorder and the role of executive functions

Abstract: Background and aims Recent research indicates that children with Developmental Language Disorder (DLD) often also score lower than their peers with typical development (TD) on tasks testing nonverbal executive functioning (EF). This study investigated whether there is evidence that children with DLD use linguistic and EF resources to support their lexical and syntactic development. Three questions were addressed: (1) How do children with DLD develop in the domains of lexicon and syntax, and how does their deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 77 publications
(140 reference statements)
8
22
0
Order By: Relevance
“…Results from the exploratory analyses indicated bi-directional influences, but with greater support for syntactic bootstrapping. Findings extend prior work suggesting that acquisition of phrase structure in school age children may allow for the more effective learning of word meanings (e.g., Blom & Boerma, 2019 ; Caglar-Ryend et al, 2019 ). The current findings complement prior behavioral studies showing reliance on lexical knowledge to facilitate grammatical development in younger children.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Results from the exploratory analyses indicated bi-directional influences, but with greater support for syntactic bootstrapping. Findings extend prior work suggesting that acquisition of phrase structure in school age children may allow for the more effective learning of word meanings (e.g., Blom & Boerma, 2019 ; Caglar-Ryend et al, 2019 ). The current findings complement prior behavioral studies showing reliance on lexical knowledge to facilitate grammatical development in younger children.…”
Section: Discussionsupporting
confidence: 79%
“…Longitudinal research using cross-lagged designs allows us to infer causal directionality ( Kearney, 2017 ). However, a shortcoming of many prior behavioral studies that have used predictive models is that they have not controlled for children’s initial skill levels (e.g., Blom & Boerma, 2019 ; Moyle et al, 2007 ). By accounting for autoregressive relations in the present study, we are able to draw better inferences about bidirectional influences in children’s semantic and syntactic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer the research question, we analyzed longitudinal data from a group of children with DLD between ages 5 and 8 years, thereby building on two previous studies about the same DLD sample as investigated for the purpose of the current study. One study demonstrated that executive functioning predicted receptive vocabulary in children with DLD (Blom & Boerma, 2019). In the other study, it was observed that children with DLD had lower outcomes on nonverbal executive functioning (Blom & Boerma, 2020).…”
Section: This Studymentioning
confidence: 98%
“…It is important to note here that a sentence recall task is not a purely syntactic task; although CELF recalling sentences performance is influenced by syntactic complexity and long-term memory representations of language (i.e., lexical knowledge; Klem et al, 2015), it is also affected by a child's verbal short-term memory (Alloway & Gathercole, 2005). Nevertheless, it is typically considered a measure of syntactic competence (e.g., Blom & Boerma, 2019;Frizelle & Fletcher, 2014).…”
Section: Measures Of Grammatical Performancementioning
confidence: 99%